1972
DOI: 10.1128/aac.1.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Microbiological Assay of Tobramycin

Abstract: Tobramycin belongs to the aminoglycoside class of antibiotics. Assay procedures were investigated to determine the most suitable methods for the assay of tobramycin in blood, urine, and pharmaceutical preparations. The agar-plate assay was the method of choice for determinations in urine and serum. The turbidimetric assay was selected for the assay of pharmaceutical preparations. An extraction technique is described that minimizes problems encountered in the estimation of tobramycin in urine. Sample diluents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Tobramycin is one of seven antibiotic factors in a complex produced by the saphrophyte Streptomyces tenebrarius [1,13,23,26]. Purification and testing of the factors in the complex revealed that tobramycin, fac tor 6, has the broadest spectrum and the strongest antibacterial effect [7].…”
Section: Introductionmentioning
confidence: 99%
“…Tobramycin is one of seven antibiotic factors in a complex produced by the saphrophyte Streptomyces tenebrarius [1,13,23,26]. Purification and testing of the factors in the complex revealed that tobramycin, fac tor 6, has the broadest spectrum and the strongest antibacterial effect [7].…”
Section: Introductionmentioning
confidence: 99%
“…Tobramycin has a good influence on Gram-negative bacteria especially many strain of the Enterobacteriaceae and Pseudomonas and also, S. aureus that have resistance against gentamicin [93]. Lamb et al (1972) reported factors that influence the microbiological assay to find the most suitable methods for the determination of tobramycin in blood, urine, and pharmaceutical preparations. Various factors such as sample diluents, pH, molarity, iron, and sodium ions were checked and the important ones were diluents, pH, and molarity.…”
Section: Tobramycinmentioning
confidence: 99%
“…For diluents effect, the results of the article showed the sensitivity of the cylinder-plate assay was increased 10 times more than the disc assay when increasing pH, therefore the dilution factor affected more on the cylinder-plate assay. By the addition of the ionic compounds like Na + and Fe 3+ in agar base, the sensitivity of tobramycin determination was decreased even though variations in pH and ion concentration were more critical for the cylinder assay, but this assay system was more reproducible and sensitive than the disc [94]. Lode et al (1975) used the agar diffusion method with B. subtilis as a test organism for the estimate of pharmacokinetic of gentamycin, sisomicin, and tobramycin.…”
Section: Tobramycinmentioning
confidence: 99%